CMOS Temperature Sensor with Programmable Temperature Range for Biomedical Applications - Agung Setiabudi; Hiroki Tamura; Koichi Tanno (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A CMOS temperature sensor circuit with programmable temperature range is proposed for biomedical applications. The proposed circuit consists of temperature sensor core circuit and programmable temperature range digital interface circuit. Both circuits are able to be operated at 1.0 V. The proposed temperature sensor circuit is operated in weak inversion region of MOSFETs. The proposed digital interface circuit converts current into time using Current-to-Time Converter (ITC) and converts time to digital data using counter. Temperature range can be programmed by adjusting pulse width of the trigger and clock frequency of counter. The proposed circuit was simulated using HSPICE with 1P, 5M, 3-wells, 0.18-μm CMOS process (BSIM3v3.2, LEVEL53). From the simulation of proposed circuit, temperature range is programmed to be 0 °C to 100 °C, it is obtained that resolution of the proposed circuit is 0.392 °C with -0.89/+0.29 °C inaccuracy and the total power consumption is 22.3 μW in 25 °C.